Dietary guidelines and school meals programmes at kindergarten In ASEAN countries / Noraishah Ahmad & Siti Noor Arisah Aziz - Ahmad, Noraishah; Aziz, Siti Noor Arisah (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2017)
The dietary guidelines are one of the guidelines that consumers need to use in ensuring their health in good conditions. The guideline has different approach and implementation for every country. Dietary guideline at kindergarten is crucial in order to maintain a good care to the kids and to nurture their future wellbeing. While the school meal program is program that has done by society or education club to make sure the kindergarten staff can adopt the program for their kids. This is also important to explore that school meal program in line with the dietary guidelines that have been set by the Ministry of Health. All of these are vital and vigorous approached in order to ensure all the kids is healthy at the early age and grow up well in the future. That is why this study aims to see what the dietary guideline is and school meals programs at kindergarten in Asian countries and what are the similarities and dissimilarities of dietary guideline and school meats programs at kindergarten in Asian countries. The information gathered by searching journal, article, books, blogs, website and other online sources from the past years publication. As for the literature, there are many programs obviously plans to the kindergarten from all over the world but since the limitation of time, only few of the programs can be discussed due to limitation of time. Although it is not many in order to cover the generalization of the countries, it is hope can be part of the new contribution to the knowledge in dietary guideline and school meals programs that that may show some good example to be implemented later in Malaysia and vice versa.